2018
DOI: 10.1002/cbic.201800153
|View full text |Cite
|
Sign up to set email alerts
|

The Alkylquinolone Repertoire of Pseudomonas aeruginosa is Linked to Structural Flexibility of the FabH‐like 2‐Heptyl‐3‐hydroxy‐4(1H)‐quinolone (PQS) Biosynthesis Enzyme PqsBC

Abstract: Pseudomonas aeruginosa is a bacterial pathogen that causes life-threatening infections in immunocompromised patients. It produces a large armory of saturated and mono-unsaturated 2-alkyl-4(1H)-quinolones (AQs) and AQ N-oxides (AQNOs) that serve as signaling molecules to control the production of virulence factors and that are involved in membrane vesicle formation and iron chelation; furthermore, they also have, for example, antibiotic properties. It has been shown that the β-ketoacyl-acyl-carrier protein synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
(150 reference statements)
1
15
0
Order By: Relevance
“…The levels of the short or especially long alkyl chain AQs appeared to be more strongly affected by prmC deficiency, whereas the effect on the medium chain lengths (C6 – C9) was less pronounced. This is in accordance with recent findings on the substrate specificity of the biosynthetic enzyme complex PqsBC, which prefers medium chain activated fatty acids over long and short chain ones [ 19 ]. Krueger et al demonstrated lower levels of PqsB and PqsC in tn prmC [ 9 ].…”
Section: Resultssupporting
confidence: 93%
“…The levels of the short or especially long alkyl chain AQs appeared to be more strongly affected by prmC deficiency, whereas the effect on the medium chain lengths (C6 – C9) was less pronounced. This is in accordance with recent findings on the substrate specificity of the biosynthetic enzyme complex PqsBC, which prefers medium chain activated fatty acids over long and short chain ones [ 19 ]. Krueger et al demonstrated lower levels of PqsB and PqsC in tn prmC [ 9 ].…”
Section: Resultssupporting
confidence: 93%
“…AQ synthesis is initiated by the coenzyme A ligase PqsA which activates anthranilic acid for the PqsD‐catalysed condensation with malonyl‐CoA to form 3‐(2‐aminophenyl)‐3‐oxopropanoyl‐CoA (2‐ABA‐CoA) Thioester hydrolysis by PqsE (which also can be mediated by unspecific thioesterases) leads to formation of 3‐(2‐aminophenyl)‐3‐oxopropanoic acid (2‐ABA), which in the next step is condensed with a fatty acid acyl‐CoA by PqsBC, leading to the 2‐alkyl‐1( H )‐quinolin‐4‐one. PqsBC has a preference for octanoyl‐CoA, leading to HHQ, but also utilizes longer and shorter acyl‐CoAs (Witzgall et al ., ). The monooxygenase PqsH hydroxylates 2‐alkyl‐1( H )‐quinolin‐4‐ones at C3, yielding PQS or derivatives (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The quinolone core is formed by action of the heterodimeric complex PqsBC. This time, CoA-activated octanoic acid is used to preload an active-site cysteine of PqsC with the fatty acid via a thioester linkage [ 30 31 ]. The previously produced 2-ABA is then consumed to from HHQ under decarboxylative condensation [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…This time, CoA-activated octanoic acid is used to preload an active-site cysteine of PqsC with the fatty acid via a thioester linkage [ 30 31 ]. The previously produced 2-ABA is then consumed to from HHQ under decarboxylative condensation [ 30 ]. Finally, PQS is produced through hydroxylation of position 3 by the NADH-dependent flavin mono-oxygenase PqsH [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation